Vapor phase growth and properties of mixed layered Pb1-xCdxI2 semiconductors - Rybak, O.V.; Chekaylo, M.V.; Pokladok, N.T. (Physics and Chemistry of Solid State, 2022)
Pb1-xCdxI2 crystals (x = 0.1; 0.9) have been obtained by crystallization from a vapour phase in a closed system at over-stoichiometric iodine vapour pressure. An alloy of CdI2 and PbI2 was used as a source of evaporation. As a result of X-ray diffraction studies, it has been found that the obtained crystals belong to 4H-polytype, the space symmetry group is P63mc. The lattice parameters and the unit cell volume of crystals have been determined: for Pb0.9Cd0.1I2 a = 4,529 Å, c = 13,96 Å, V = 247,9 Å3; for Pb0.1Cd0.9I2 a = 4.258 Å, c = 13.70 Å, V = 215.0 Å3. The morphology of Pb1-xCdxI2 solid solutions crystals has been studied by scanning electron microscopy. Grown light orange Pb0.9Cd0.1I2 crystals have the shape of plates and ribbons, the surface of which is sculpted by growth figures. The transparent mixed Pb0.1Cd0.9I2 crystals have been grown from the vapour phase only in the form of plates. The spectral dependences of the optical absorption of Pb1-xCdxI2 crystals at room temperature have been studied. The optical widths of the band gaps of the grown crystals have been determined from the absorption spectra using the Tauc relation.